La prosa de Adolfo Bioy Casares: el poder de la sátira, la sátira del poder - Previtera, Roberta (Philologia Hispalensis, 2013)
In Bioy Casares’s fiction a strong presence of humor can be detected. Firstly, we study how humor appears in the texts, focusing on the strategies utilized in the text. In this way we establish a link between humor and irony. Later, we introduce the concept of satire and we analyze the relation between irony and evaluation of contemporary politic context.